2011
DOI: 10.1177/0269215510390719
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dynamic ankle-foot orthoses in chronic stroke patients at three-month follow-up: a randomized controlled trial

Abstract: Chronic hemiparetic patients may benefit from using dynamic ankle-foot orthosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 36 publications
0
69
0
4
Order By: Relevance
“…659 A recent meta-analysis and systematic review suggested the potential mechanism(s) associated with the above effects by demonstrating a positive effect of an AFO on ankle kinematics, knee kinematics in stance phase, kinetics, and energy cost. 658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis.…”
Section: Level Of Evidencementioning
confidence: 99%
“…659 A recent meta-analysis and systematic review suggested the potential mechanism(s) associated with the above effects by demonstrating a positive effect of an AFO on ankle kinematics, knee kinematics in stance phase, kinetics, and energy cost. 658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis.…”
Section: Level Of Evidencementioning
confidence: 99%
“…En cuanto al uso de otros productos de apoyo como el bastón, se permitió el uso del bastón en algunos estudios 17,67,69,71,72 , en otro no se permite su uso 70 y en tres no se especificó 56,57,61 .…”
Section: Resultados Descripción De Los Estudiosunclassified
“…Se escribió a través de correo electró-nico a trece autores 38,55-66 solicitando aclaración acerca de algunos aspectos del diseño o información no indicada con el fin de completar las evaluaciones de calidad. Seis autores proporcionaron los datos solicitados [56][57][58][59][60][61] . Para el resto de los estudios solo se usaron los datos publicados.…”
Section: Calidad Metodológicaunclassified
“…Various studies have reported the positive effects of AFOs on the walking ability in hemiplegic pa-H CrossMark tients [4,5]. AFOs also help patients in both stance and swing phases of gait by stabilizing ankle-foot complex and preventing abrupt foot drop [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although Solid AFO (SAFO) enhances walking speed in hemiplegic patients, the acquired speed is far less than that of the healthy subjects [9]. Thus, some efforts have been done to increase gait velocity with common SAFO [7,[10][11][12]. Considering the positive effect of rocker bar modification added to orthoses on walking velocity reported in previous studies [13][14][15], we hypothesized that adding rocker bar to a SAFO could potentially improve walking speed in hemiplegic patients.…”
Section: Introductionmentioning
confidence: 99%